Relative risk of knee chondrocalcinosis in siblings of index cases with pyrophosphate arthropathy. Issue 8 (12th July 2004) - Zhang, W; Neame, R; Doherty, S; Doherty, M
Abstract : Objectives: To examine the genetic contribution to common, apparently sporadic, radiographic knee chondrocalcinosis (CC) and pyrophosphate arthropathy (PA). Method: (1) Design: radiographic sibling study. Comparison of the prevalences of knee CC and PA in siblings of index cases with PA with those in the community. (2) Subjects: 80 index cases with PA listed for total knee replacement; 122 of their siblings aged ⩾40 years; and 1729 participants from community knee pain surveys who had undergone knee radiographs. (3) Main outcome measure: odds ratios of knee CC and PA in siblings versus community participants. Results: The prevalence of knee CC was 13% (15/116) in the siblings and 6.9% (119/1727) in the community participants. The adjusted odds ratio (aOR) was 1.2, 95% confidence interval (CI) 0.6 to 2.3. The main risk factors for knee CC were age, knee pain, and knee OA. The prevalence of knee PA was 7% (9/122) in the siblings and 3.4% (59/1729) among the community participants (aOR = 1.1, 95% CI 0.4 to 2.7). The main risk factors for PA were age and knee pain. The age, sex, and knee pain standardised prevalence of PA in the Nottingham community aged ⩾40 was 2.40%. Conclusion: The risk of knee CC and PA in siblings of index cases with PA is no higher than that in the general population. Although rare familial CC is recognised, this study suggests that no major genetic predisposition to CC occurs in common symptomatic knee OA.